2021
DOI: 10.1161/circresaha.120.317685
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Analysis of Extracellular Matrix Remodeling in the Failing Heart

Abstract: Rationale: Cardiac extracellular matrix (ECM) comprises a dynamic molecular network providing structural support to heart tissue function. Understanding the impact of ECM remodeling on cardiac cells during heart failure (HF) is essential to prevent adverse ventricular remodeling and restore organ functionality in affected patients. Objective: We aimed to (i) identify consistent modifications to cardiac ECM structure and mechanics that contribute to HF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 53 publications
3
61
0
Order By: Relevance
“…A recent publication by Perestrelo et al [25] added additional information to the puzzle of ECM remodeling. In their clinical and experimental decellularized samples of failing myocardium, they identified a common pattern of aligned, flat, and compact fiber bundles with reduced elasticity and organizational complexity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Perestrelo et al [25] added additional information to the puzzle of ECM remodeling. In their clinical and experimental decellularized samples of failing myocardium, they identified a common pattern of aligned, flat, and compact fiber bundles with reduced elasticity and organizational complexity.…”
Section: Discussionmentioning
confidence: 99%
“…A versatile decellularization protocol working efficiently on distinct organs and also on the same tissue but on different ontogenetic stages (young and adult tissues) or health status has been recently reported (Silva et al, 2016(Silva et al, , 2019Garlikova et al, 2017;Pinto et al, 2017). This approach mitigates differences resultant from the application of distinct decellularization protocols, allowing fair comparisons on ECM composition and functional alterations across tissues, age, and normalcy vs. disease status (Perestrelo et al, 2020). Decellularization can be performed on tissues/organs or on cells cultured in vitro as monolayers or aggregates (Beacham et al, 2007;Nair et al, 2008).…”
Section: Decellularization As a Methodology To Deconstruct Ecm Composition Structure And Bioactivitymentioning
confidence: 99%
“…Thus far we have shown that cardiac ECM pathological remodeling induces hnRNPC shuttling to the active sites of translation at the sarcomere. Pathological remodeling is a complex phenomenon modifying the chemical composition and the mechanical properties of cardiac ECM 5,23 . We tried to disentangle the role of mechanical cues in hnRNPC localization.…”
Section: Resultsmentioning
confidence: 99%